Isolation and characterization of Toxoplasma gondii from captive caracals (Caracal caracal). (December 2020) - Jiang, Nan; Xin, Shilin; Li, Junbao; Su, Chunlei; Zhang, Longxian; Yang, Yurong
Abstract: Toxoplasma gondii infects most warm-blooded animals, including humans. Felids can serve as both intermediate and definitive hosts for T. gondii . However, there is no direct evidence to prove the caracal ( Caracal caracal ) is an intermediate host for T. gondii . Here, we report T. gondii infection in two caracals in a zoo from China. Antibodies against T. gondii were found in both caracals by modified agglutination test (MAT) (cut-off titer: 1:25). Tissue cysts were observed in the leg and tongue muscles of caracal case # 1. These cysts were confirmed as T. gondii by immunohistochemical staining and T. gondii was detected by polymerase chain reaction (PCR). Viable T. gondii strain was isolated from the striated muscles of caracal case # 2 and designated as TgCaracalCHn1. DNA from tachyzoites obtained from cell cultures was characterized by RFLP-PCR using ten markers ( SAG1, SAG3, SAG2, BTUB, c22-8, GRA6, c29-2, PK1, L358, and Apico ) and the virulence genes ( ROP5 and ROP18 ). The results indicate that this isolate belongs to ToxoDB genotye #2 (Type III). The virulence of this isolate was evaluated in BALB/c mice. A dose of 10 4 TgCaracalCHn1 tachyzoites was non-lethal to mice. Tissue cysts were found in brain tissues of infected mice. This result confirmed that the TgCaracalCHn1 is non-virulent to mice. Current study documents first isolation of viable T. gondii strain from caracal and also indicates that caracal can act as new intermediate host for T. gondii . Graphical abstract: Image 1 Highlights: T. gondii infection in caracals was detected and confirmed by serological and molecular analysis, immunohistochemistry, and bioassay in mice. One viable T. gondii strain was isolated from caracal and designated as TgCaracalCHn1, ToxoDB#2. This report provides direct evidence of caracal as an intermediate host of T. gondii.